UPLC–MS-Based Non-targeted Analysis of Endogenous Metabolite Changes in the Leaves of Scabiosa tschiliensis Grüning Induced by 6-Benzylaminopurine and Kinetin - Du, Jialin; Ma, Weiwei; Li, Yi; Lu, Xu; Geng, Zhaopeng; Huang, Hangjun; Yuan, Yuanyuan; Liu, Yue; Wang, Xiaodong; Wang, Junli (Frontiers in Plant Science, 2021)
In vitro propagation technology with plant growth regulators (PGRs) is generally applied in the cultivation of S. tschiliensis, which can solve collection difficulties and limited resources of S. tschiliensis. Nevertheless, comprehensive metabolomic evaluation on S. tschiliensis with PGRs effects is still lacking. In this work, a non-targeted metabolomics approach, coupled with statistical and pathway enrichment analysis, was used to assess the regulatory influences of 6-benzylaminopurine (6-BA) and kinetin (KT) applied in S. tschiliensis. The results showed that the PGRs affect metabolism differentially, and the addition of 6-BA and KT can increase different secondary metabolites. In the two PGR groups, some primary metabolites such as L-phenylalanine, L-tyrosine, L-arginine, L-asparagine and D-proline were significantly reduced. We suspect that under the action of PGRs, these decreased amino acids are derived into secondary metabolites such as umbelliferone, chlorogenic acid and glutathione. Additionally, some of those secondary metabolites have biological activity and can also promote plant growth. Our results provide a basis for the targeted cultivation and utilization of S. tschiliensis, especially the expression of metabolites related to PGR application.